Guanidine electron donors and silver halides: interplay and competition between redox, coordination and polymerization reactions - Emeljanenko, Dimitri; Horn, Julian; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2012)
Redox reactions compete with coordination and polymerization reactions when the organic electron donor and ligand, 1,2,4,5-tetrakis(tetramethylguanidino)benzene (1), is dissolved together with silver halides AgX (X = Cl, Br or I) in solvents of different polarity. The complex results obtained for the relatively simple system 1/AgX highlight the importance of solvent effects. A variety of chain polymers have been synthesized in which the guanidine electron-donor building blocks are connected by silver halide clusters of different sizes.